COMPUTER SIMULATION AS A SUPPORT OF INDEPENDENT WORK OF STUDENTS IN STUDING THEORETICAL PHYSICS - O.A. Konoval; T.I. Turkot (Ìнформаційні технології в освіті)
The article reveals advantages of the process of self-study with use of computer didactic means, distinguishes didactic facilities of computer educational programs as to modeling of physical processes on the example of tasks in electrodynamics for self study of students with applying of the program «Component». It is offered examples of tasks for self study in electrodynamics for students with applying of the program «Component».